The Anatomical Boundary of the Rat Claustrum - Dillingham, Christopher M.; Mathiasen, Mathias L.; Frost, Bethany E.; Lambert, Marie A. C.; Bubb, Emma J.; Jankowski, Maciej M.; Aggleton, John P.; O’Mara, Shane M. (Frontiers in Neuroanatomy, 2019)
The claustrum is a subcortical nucleus that exhibits dense connectivity across the neocortex. Considerable recent progress has been made in establishing its genetic and anatomical characteristics, however a core, contentious issue that regularly presents in the literature pertains to the rostral extent of its anatomical boundary. The present study addressed this issue in the rat brain. Using a combination of immunohistochemistry and neuroanatomical tract tracing, we have examined the expression profiles of several genes that have previously been identified as exhibiting a differential expression profile in the claustrum relative to the surrounding cortex. The expression profiles of parvalbumin (PV), crystallin mu (Crym), and guanine nucleotide binding protein (G protein), gamma 2 (Gng2) were assessed immunohistochemically alongside, or in combination with cortical anterograde, or retrograde tracer injections. Retrograde tracer injections into various thalamic nuclei were used to further establish the rostral border of the claustrum. Expression of all three markers delineated a nuclear boundary that extended considerably (~500 µm) beyond the anterior horn of the neostriatum. Cortical retrograde and anterograde tracer injections, respectively, revealed distributions of cortically-projecting claustral neurons and cortical efferent inputs to the claustrum that overlapped with the gene marker-derived claustrum boundary. Finally, retrograde tracer injections into the thalamus revealed insular cortico-thalamic projections encapsulating a claustral area with strongly diminished cell label, that extended rostral to the striatum.